Burnout, Psychological Symptoms, and Secondary Traumatic Stress Among Midwives Working on Perinatal Wards: A Cross-Cultural Study Between Japan and Switzerland - Oe, Misari; Ishida, Tetsuya; Favrod, Céline; Martin-Soelch, Chantal; Horsch, Antje (Frontiers in Psychiatry, 2018)
The aim of this study was to explore the cross-cultural differences of burnout, symptoms of anxiety, depression, and secondary traumatic stress between an Eastern (Japan) and a Western (Switzerland) country. One hundred seventy midwives participated in the study. There were significant differences in age group (χ2 (3) = 24.2, p < 0.01), marital or relationship status (χ2 (2) = 28.4, p < 0.01), and years of experience (χ2 (2) =17.8, p < 0.01) between the two countries. The Japanese staff were younger, more often unmarried, and had less experience than the Swiss staff. The mean score of depersonalization was significantly higher in Switzerland (4.8 ± 3.8) than in Japan (3.2 ± 3.7; |z| = 2.71, p < 0.01). The mean score of general psychological distress in the Swiss sample (12.8 ± 6.5) was significantly higher than those in the Japanese sample (10.3 ± 6.2; |z| = 2.04, p = 0.04). In addition, the mean score of secondary traumatic stress was higher in the Swiss sample (31.8 ± 9.7) than in the Japanese sample (24.1 ± 8.6; |z| = 4.56, p < 0.01). These results may reflect cultural differences such as working conditions or family environment between Japan and Switzerland.